БУЯНТ-УУЛЫН ИЛРЭЛИЙН ХАЙЛУУР ЖОНШНЫ ХИЙ ШИНГЭНИЙ ОРМЫН СУДАЛГААНЫ ҮР ДҮН - С.ДАНДАР; Д.ОЮУНЦЭЦЭГ; Н.МӨНХБИЛЭГ; Н.БАЙГАЛМАА (Geological Issues, 2023)
БУЯНТ-УУЛЫН ИЛРЭЛИЙН ХАЙЛУУР ЖОНШНЫ ХИЙ ШИНГЭНИЙ ОРМЫН СУДАЛГААНЫ ҮР ДҮН